Entomopathogenic fungi of soils of freshwater swamps, tidal lowlands, peatlands, and highlands of South Sumatra, Indonesia - AYU SAFITRI; SITI HERLINDA; ARUM SETIAWAN (Society for Indonesian Biodiversity, 2018)
Safitri A, Herlinda S, Setiawan A. 2018. Entomopathogenic fungi of soils of freshwater swamps, tidal lowlands, peatlands, and highlands of South Sumatra, Indonesia. Biodiversitas 19: 2365-2373. Ecosystems of lowlands and highlands in South Sumatra have specific characteristics of soils and vegetations that can affect the availability of entomopathogenic fungi. This study aimed to explore and identify species and to determine inoculum potentials of the entomopathogenic fungi from soils of freshwater swamps, tidal lowlands, peatlands, and highlands. Baiting of entomopathogenic fungi on soil samples used the larvae of Tenebrio molitor. The entomopathogenic fungi species found in this research were Beauveria bassiana and Metarhizium anisopliae. The number of the fungal isolates were 30 isolates consisting of nine isolates of B. bassiana and 21 isolates of M. anisopliae.The highest number of isolates was found in the highland ecosystem (11 isolates) and the lowest was found in peatland ecosystem (4 isolates). The highest percentage average of inoculum potentials of the fungi was found in the high land ecosystem (4.04%) and the lowest one was found in freshwater swamps ecosystem (2.11%). Based on the vegetation type, the soil planted with mustard in Talang Patai-Pagaralam (highland ecosystem) had the highest inoculum potentials (9.33%). These fungi will make an important contribution to the biological control for insect pests in lowland to highland ecosystems in Indonesia.